The Abolitionist's Journal : Memories of an American Antislavery Family - Richardson, James, 1953- (Book collections on Project MUSE., 2022)
"The Abolitionist's Journal is a skillfully researched and deeply engrossing story centering on the life and times of the author's great-great grandfather, George Richardson (1824-1911)--a fervently abolitionist preacher who offered shelter to runaway slaves on the Underground Railroad, served as a chaplain in the Union Army during the Civil War, and founded a school in Texas for freed black slaves after the war, which still stands today as a testament to his extraordinary life. The book weaves his story with the selfdiscovery of how the author's ancestor's life has intersected with his own. "The book opens with the George Richardson's handwritten journal that sat unread on my father's bookshelf for decades until the weekend before I entered seminary in midlife to become an Episcopal priest. After reading the journal, my life was never the same again. "George Richardson filled his pages with stories of war, white vigilantes, Black schools, church politics and frontier congregations. He wrote of adventures at Yellowstone in the early years of the national park. He wrote of getting lost on horseback in Minnesota in the winter, and the crushing devastation in the Mississippi countryside in the days after the Civil War. He wrote of life in Black shantytowns, Texas Panhandle cowboys and Idaho Mormons. His is the story of our country. "After reading the journal, my wife Lori and I began retracing the steps through eight states of George and his wife Caroline Richardson (1825-1887), visiting graveyards, battlefields, schools, churches and the house they used on the Underground Railroad. "Our journey has brought me to the brink of the racial divide in America. The book raises uncomfortable questions about why a family that was committed to racial equality in the mid-nineteenth century lost that commitment in the twentieth century. The book covers my years as a journalist covering the resurgent Ku Klux Klan in Southern California, and later serving as a church pastor in Charlottesville, invaded by neoNazis thrusting this college town into the national spotlight.""--